1986
DOI: 10.1177/0038038586020001004
|View full text |Cite
|
Sign up to set email alerts
|

Credentials and Careers: Some Implications of the Increase in Professional Qualifications amongst Women

Abstract: Although the extent of women's participation in the formal economy has grown considerably since the Second World War, it is a well-established fact that this increase has not been evenly distributed throughout the occupational structure. Women who work tend to be concentrated either into `women's' occupations or other low-level jobs. One reason for this, it has been argued, is that women have historically failed to acquire formal work-related qualifications. A preliminary model is developed relating specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(26 citation statements)
references
References 4 publications
0
25
0
1
Order By: Relevance
“…(Chef 9) Throughout the course of the fieldwork, discussions with the chefs revealed that this violent and aggressive means of induction is often regarded as being analogous with the means of induction to the military. In both the restaurant industry and the military, the same notions exists of 'building' a functioning member of a unit by means of the initial removal of their previous behaviour patterns, followed by the subsequent rebuilding of these behaviour patterns to conform to those required by the organisation (Salin & Hoel, 2011) Crompton & Sanderson (1986) term 'gendered niches' such as the salads or the pastry section (Burrow et al, 2015). To conclude, it can be argued that the survival of the young chefs' induction and socialisation 21 denotes compatibility and ability to integrate as well as a way to demonstrate loyalty and commitment to the head chef and the rest of the kitchen brigade (Burrow et al, 2015).…”
Section: Occupational Socialisationmentioning
confidence: 99%
“…(Chef 9) Throughout the course of the fieldwork, discussions with the chefs revealed that this violent and aggressive means of induction is often regarded as being analogous with the means of induction to the military. In both the restaurant industry and the military, the same notions exists of 'building' a functioning member of a unit by means of the initial removal of their previous behaviour patterns, followed by the subsequent rebuilding of these behaviour patterns to conform to those required by the organisation (Salin & Hoel, 2011) Crompton & Sanderson (1986) term 'gendered niches' such as the salads or the pastry section (Burrow et al, 2015). To conclude, it can be argued that the survival of the young chefs' induction and socialisation 21 denotes compatibility and ability to integrate as well as a way to demonstrate loyalty and commitment to the head chef and the rest of the kitchen brigade (Burrow et al, 2015).…”
Section: Occupational Socialisationmentioning
confidence: 99%
“…These factors, in turn, effect the ways in which women are seen as suitable for managerial positions, the extent to which they are likely to be concentrated within particular occupations and confined to various functional specialisms. Some economic sectors are more 'feminized' than others and in the more highly feminized sectors, it may be possible for them to pursue occupational rather than organizational careers (Crompton and Sanderson, 1986) and hence, to be more mobile within labour markets. In these sectors, it could be that women acquire general managerial skills which enhance their opportunities for obtaining senior corporate positions.…”
Section: Richard Scase and Robert Coffeementioning
confidence: 99%
“…As a result, much discussion relies upon untested assumptions rather than rigorously-conducted social investigation. This is surprising and unacceptable given the increasing number of highly qualified women who are employed in managerial and professional occupations world-wide (Crompton and Sanderson, 1986;Nicholson and West, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…An almost impenetrable mystique has grown up around the rate support and block grant systems -indeed, the frequency with which we were told it suggests that every treasurer has the same favourite joke, namely that only two people ever really understood the system, he -despite an increased feminisation at lower levels in recent years (see Crompton and Sanderson, 1986) chief finance officers are almost invariably male -is one and the other is now in a mental hospital .…”
Section: So Far We Have Concentrated On the Politics Of The Local Autmentioning
confidence: 99%